Sensorless stepwise breakthrough detection technique for safe surgical drilling of bone - Pinyo Puangmali (2020)
© 2019 In bone surgery, drilling of bone without causing severe damage to tissue is a critical procedure. Particularly for skull, spine, and special kinds of orthopedic surgeries, the process of bone drilling requires high accuracy and precision since excessive drill protrusion can cause damage to nerves, blood vessels, and nearby organs. To enhance safety of drilling, a new breakthrough detection technique that does not require the installation of a sensor for force or torque measurement is proposed. This technique relies only on the measurement of current flowing through the motor of an electric drill to monitor drilling progress. By measuring the amount of current while executing stepwise drilling and applying a hysteresis thresholding algorithm, the breakthrough event can be effectively identified in real-time. Experimental tests of a drill prototype utilizing this scheme showed that breakthrough could be consistently detected. This prevents over drilling, enabling reliable drilling operation which can minimize tissue damage.